Consistency, accountability, and transparency in mosque financial management based on psak no. 109 (case study of the mosque in bandar khalipah village) - Muhammad Irvan Fauzi; Hendra Harmain (Institute of Computer Science (IOCS), 2023)
This study aims to determine consistency, accountability, and transparency in the financial management of mosques in Bandar Khalipah Village as reviewed based on PSAK 109. The objects of this research are 3 mosques located in Bandar Khalipah Village namely Al-Ishlah Mosque, Babussalam Mosque, and Miftahul Iman Mosque. The type of research used in this research is descriptive qualitative research. Data sourced from primary data and secondary data with data collection techniques used in this study are documentation, field observations, and interviews. Based on the results of this study it can be concluded that the financial reports at Al-Ishlah Mosque, Babussalam mosque, and Miftahul Iman mosque as a whole are not in accordance with PSAK 109 because of several problems or obstacles found, namely the lack of information about PSAK 109 and the lack of ability of managers to make reports financial statements in accordance with PSAK 109.